Rise Of Intraocular Pressure After Nd: YAG Laser Capsulotomy - Asma Shams; Narain Das; Jai Kumar; Beenish Khan; M. Nasir Bhatti; Anas Bin Tariq; Adnan Anwar (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: Posterior capsule opacification (PCO) after cataract is a common complication of extra capsular cataract extraction with or without intraocular lens implantation. Aim of this study was to evaluate changes in intraocular pressure after Nd-Yag laser posterior capsulotomy for PCO. Methodology: This retrospective study using convenient sampling technique was done at Eye Department of Shaheed Mohtarma Benazir BhuttoMedical College Lyari, Sindh Government General Hospital, Karachi for six months (1st January 2020 to 30th June 2020. After ethical approval and informed permission from patients and guardian, data was collected and analyzed by SPSS version 20 and presented by calculating mean and standard deviation for quantitative data and frequency and percentages for qualitative data. Results: Total 50 patients (20 males and 30 females) were studied where 22 right and 28 left eyes. Mean age was 59.08 years. Mean pre-operative IOP was 13.28 and 13.12 mmHg of right and left eye respectively (Table I). At 2 hours mean IOP was 16.84±3.63 mmHg and after one week 12.48±2.0 mmHg. Base line pre-laser IOP was measured by Goldman Applanation Tonometer (GAT) and slit lamp examination. Pupils were dilated using 1% tropicamide eye drops. IOP was evaluated immediate post-procedure, two hours post-procedure and one week from date of laser. Conclusion: Nd -Yag laser capsulotomy is treatment of choice for PCO and associated with complications like Raised Intraocular Pressure (IOP), Intraocular lens pitting, cystoid macular oedema, retinal detachment. Raised IOP is most common complication and prescribing anti-glaucoma drugs in order to decrease intraocular pressure.